Edukasi Penerapan Penggunaan Teknologi yang Bijak terhadap Perilaku Anak Usia Dini - Sakina Sakina; Neneng Hasanah; Astuti Astuti; Risa Yuliani; Siti Masitohe (Universitas Pamulang, 2020)
Gadget is a technology that has a function to facilitate communication for humans. The use of gadgets in the world of education is very influential, especially in finding information and facilitating the learning process of students. However, advances in gadget technology for the world of education also have a negative impact, which can cause students to be lazy to study and play gadgets more often not on time. Service to the Community Pamulang University conducts one of the outreach activities regarding